Analysis of fintech implementation strategy in sharia bank financing (case study at BSI KCP Cemara Asri) - Vingkan Andini; Aqwa Naser Daulay; Nur Ahmadi Bi Rahmani (Indonesia Auditing Research Journal, 2026)
This study aims to analyze the strategy of implementing financial technology (fintech) in Islamic bank financing at BSI KCP Cemara Asri. The study used a qualitative descriptive approach with a case study method and a SWOT analysis as a strategic analysis tool. Research data was obtained through questionnaires to 9 respondents consisting of bank employees and customers using fintech-based financing services, and supported by documentation data from official reports and related literature. The analysis results show that the IFAS matrix value is 2.40 and EFAS is 2.00, indicating that internal and external conditions are in the moderate category. The SWOT matrix mapping places BSI KCP Cemara Asri in Quadrant III, indicating the need for a turnaround strategy by strengthening internal factors to capitalize on external opportunities. The IE matrix analysis places the organization in Quadrant V with a hold and maintain strategy. The research findings indicate that the application of fintech in Islamic bank financing has great potential to improve service efficiency and expand financing access, but requires strengthening aspects of digital literacy, human resource competency, and digital system security for optimal fintech implementation.